The Circular Economy Challenge: Towards a Sustainable Development - Amato, Alessia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Many recent events, including the COVID-19 pandemic and climate change, have proven the necessity of a transformation of the current economic system based on a linear schema of: "take", "make", "use", and "dispose". This radical change should involve all of the actors involved in the economic system: institutions, industries, consumers, and scientific research. Only cooperation among these stakeholders can ensure an effective shift toward a circular model. However, which kinds of actions can be performed to implement an effective circular economy? The present Special Issue collects nine papers that prove the possibility of implementing the circular economy from different points of view. The authors analyze all of the spheres of sustainability (environmental, economic, and social) in a variety of contexts, evaluating the effect of the circular choices. The nine papers include several key product value chains, in agreement with the most recent European Circular Economy Action Plan (e.g., electronics and ICT, batteries, plastics, construction and buildings, and food). The present paper collection proves that the circular economy is not only a simple business model, but rather, it involves the integration of many strategies for the protection of the natural ecosystem and the maintenance of worldwide economic stability. The holistic approach is essential for a successful business model, and innovation has an indispensable role in the transition. In this context, the present Special Issue aims to be a multidisciplinary collection of innovations useful for all of the stakeholders involved in the circular economy.